2008
DOI: 10.1021/ol802466t
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (+)-Psymberin (Irciniastatin A): Catalytic Reagent Control as the Strategic Cornerstone

Abstract: An effective total synthesis of the marine sponge cytotoxin (+)-psymberin [irciniastatin (1)] has been achieved. Highlights of the strategy include a Diels-Alder reaction between a bissiloxy diene and an allene to construct the aromatic ring, a boron-mediated aldol to elaborate the C(15-17) all syn stereotriad, catalytic reagent control to set the C(8, 9, 11 and 13) stereogenic centers of the tetrahydropyran core, and a late-stage Curtius rearrangement to install the sensitive N,O-aminal moiety. The synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 26 publications
0
38
0
4
Order By: Relevance
“…This concept was addressed in the synthesis of key intermediate 51 in the total synthesis of (+)-tedanolide (52). Reaction of aldehyde 50 with 4-substituted vinylogous ketene acetal (49) gave rise to VMAR adduct 51 with the entire setup of the C4 and C5 geometry of this key intermediate, namely the all-syn-aldol product (Felkin-Anh control) (Scheme 2.12) [27].…”
Section: Ester-derived Silyl Dienol Ethers -Diastereoselective Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…This concept was addressed in the synthesis of key intermediate 51 in the total synthesis of (+)-tedanolide (52). Reaction of aldehyde 50 with 4-substituted vinylogous ketene acetal (49) gave rise to VMAR adduct 51 with the entire setup of the C4 and C5 geometry of this key intermediate, namely the all-syn-aldol product (Felkin-Anh control) (Scheme 2.12) [27].…”
Section: Ester-derived Silyl Dienol Ethers -Diastereoselective Processesmentioning
confidence: 99%
“…A very prominent example is tryptophane-based B-phenyloxazaborolidinone 103, mediating the asymmetric VMAR between unsubstituted silyl ketene O,O-acetal (32) one of the key steps performed in the total synthesis of (+)-psymberin (105), alias irciniastatin A (Scheme 2.25) [52]. The yield of the vinylogous aldol product 104 was only 66%, but with an almost complete enantiocontrol in favor of the desired R-isomer.…”
Section: Ester-derived Silyl Dienol Ethers -Enantioselective Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Later De Brabander and coworkers 7 and Xianhai and coworkers 8 synthesized and made a complete stereochemical assignment of psymberin with an S -configuration at C4 and they concluded that psymberin and irciniastatin A were structurally identical. Other synthetic approaches to psymberin were attempted by Smith 9 , Crimmins 10 as well as an interesting approach to the amide side chain by Iwabachi. 11 Recently Smith 12 and De Brabander 13 have also developed a second generation synthesis of this family of natural products.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction also worked for the formation of 5-membered rings although the amount of acetate-derived product increased (entry 12). When bulky nucleophiles were used (entries 13,14), the acetate was isolated as the only product. The diastereoselectivity of the five-member ring formation was surprisingly good with only one diastereomer being isolated.…”
Section: Introductionmentioning
confidence: 99%